Oligo/Amenorrhea Is an Independent Risk Factor Associated With Low Ovarian Response - Hu, Kai-Lun; Gan, Kwanghann; Ying, Yue; Zheng, Junyan; Chen, Ruixue; Xue, Jinglei; Wu, Yiqing; Liu, Yifeng; Zhu, Yimin; Xing, Lanfeng; Zhang, Dan (Frontiers in Endocrinology, 2021)
Capsule Oligo/amenorrhea is an independent risk factor of low ovarian response but not high ovarian response, particularly in women with low AMH levels. Objective To investigate the association of menstrual cycle length (MCL) with anti-Müllerian hormone (AMH) and ovarian response. Methods This was a retrospective cohort study. A total of 7471 women who underwent ovarian stimulation and oocyte retrieval were enrolled. The main outcome was the number of oocytes retrieved. Main Results A total of 5734 patients were eligible for analysis. In women without polycystic ovary syndrome (PCOS), serum AMH levels and antral follicle count were significantly lower in women with short cycles and higher in women with oligo/amenorrhea than those with a normal menstrual cycle. In women with PCOS, compared to women with a normal menstrual cycle, women with short cycles and women with oligo/amenorrhea showed higher antral follicle count and higher serum AMH levels. Compared with the 0-25th range group of AMH levels, 75-100th percentile groups showed a significantly increased rate of oligo/amenorrhea in women with and without PCOS [adjusted odds ratio (OR) =1.9 (1.04, 3.46), 2.4 (1.70, 3.35)]. In women without PCOS, the low ovarian response was more common in women with short cycles and less common in women with oligo/amenorrhea compared to women with normal cycles [OR=3.0 (2.38, 3.78), 0.7 (0.55, 0.96), respectively]. When adjusted for AMH levels, both short cycles and oligo/amenorrhea were associated with an increased risk of low response [adjusted OR=1.3 (1.02, 1.75), 1.3 (0.93, 1.86), respectively]. In women without PCOS and with low AMH levels, the low ovarian response was more common in women with short cycles as well as in women with oligo/amenorrhea [OR=1.5 (1.08, 1.98), 1.7 (1.08, 2.69), adjusted OR=1.2 (0.86, 1.74), 2.2 (1.31, 3.82), respectively]. Conclusion AMH levels are significantly associated with increased risk of oligo/amenorrhea in women with and without PCOS. AMH is an indispensable confounder in the association between MCL and ovarian response in women without PCOS. Oligo/amenorrhea is an independent risk factor associated with a low ovarian response in women without PCOS, particularly those with low AMH levels.